Capital Structure, Liquidity, and Financial Performance on The Quality of Earnings - Diyah Santi Hariyani; Fika Pratama, Bella; Hasanah, Karuniawati (Neo Journal of economy and social humanities, 2022)
Interested parties consider financial statements necessary because they can analyze the company's profit level. This study aims to provide empirical evidence on the effect of capital structure, liquidity, and financial performance on the quality of earnings in manufacturing companies listed on the IDX in 2019-2021. The sample used in this study was 77 companies with a purposive sampling technique to obtain 231 data. The method used is quantitative, and then the data collected is analyzed using the IBM SPSS version 25 software program. The results show that the capital structure and liquidity variables significantly affect earnings quality. At the same time, the Return on Assets (ROA) variable has no significant effect on earnings quality